Nanopatterning Hexagonal Boron Nitride with Helium Ion Milling: Towards Atomically-Thin, Nanostructured Insulators. (1st February 2018) - Gilbert, S. Matt; Liu, Stanley; Schumm, Gabe; Zettl, Alex
ABSTRACT: In this report, we demonstrate the use of helium ion milling for the controllable fabrication of nanostructures in few-layer hexagonal boron nitride (h-BN). Using the direct-write lithographic capabilities of a scanning helium ion microscope (HIM), nanopores with diameters as small as 4 nm and nanoribbons with widths of 3 – 10 nm are etched from suspended h-BN sheets. This ability to pattern h-BN sheets with high-throughput and sub-10 nm precision paves the way for future studies that make use of atomically-thin, nanostructured insulators such as those needed for nanopore sequencing and patterned van der Waals heterostructures.